Assessment of tidal volume and gas leak during mask ventilation of preterm infants in the delivery room. Issue 6 (14th June 2010) - Schmölzer, Georg M; Kamlin, Omar C O F; O'Donnell, Colm P F; Dawson, Jennifer A; Morley, Colin J; Davis, Peter G
Abstract : Aim: The aim was to compare resuscitators' estimates of tidal volume (VT ) and face mask leak with measured values during positive pressure ventilation (PPV) of newborn infants in the delivery room. Patients and methods: The authors measured inflating pressures and VT delivered using a respiratory function monitor, and calculated face mask leak. After 60 s of PPV, resuscitators were asked to estimate VT and face mask leak. These estimates were compared with measurements taken during the previous 30 s. Results: The authors studied 20 infants who received a mean (SD) of 21 (6) inflations during the 30 s. The median (IQR) expired tidal volume (VTe ) delivered was 8.7 ml/kg (5.3–11.3). VTe varied widely during each resuscitation and between resuscitators. Five resuscitators could not estimate VTe, one overestimated and 14 underestimated their median delivered VTe . The median (IQR) face mask leak was 29% (16–63%). Leak also varied widely during each resuscitation and between resuscitators. One resuscitator could not estimate mask leak, four overestimated leak and 15 underestimated leak. Conclusion: During face mask ventilation in the delivery room, VT and face mask leak were large and variable. The resuscitators were unable to accurately assess their face mask leak or delivered VT .